Immunization with Genetic Toxoids of the Arcanobacterium pyogenes Cholesterol-Dependent Cytolysin, Pyolysin, Protects Mice against Infection - Jost, B. Helen (American Society for Microbiology, 2003)
Pyolysin (PLO), a cholesterol-dependent cytolysin expressed by Arcanobacterium pyogenes, is an important host-protective antigen. However, this molecule is toxic and requires inactivation prior to its use as a vaccine. Three genetically toxoided, nonhemolytic PLO molecules, HIS-PLO.F(497), HIS-PLO.ΔP(499), and HIS-PLO.A(522), were found to be nontoxic, and vaccinated mice were protected from infection, indicating the potential of these toxoids as vaccines. Furthermore, in a mouse model of infection, A. pyogenes carrying the F(497) mutation was as attenuated as a PLO-deficient strain, indicating that the cytolytic activity of PLO is important in virulence.